Molecular evolution of the MAGUK family in metazoan genomes - te Velthuis, Aartjan JW (BioMed Central, 2007)
BACKGROUND: Development, differentiation and physiology of metazoans all depend on cell to cell communication and subsequent intracellular signal transduction. Often, these processes are orchestrated via sites of specialized cell-cell contact and involve receptors, adhesion molecules and scaffolding proteins. Several of these scaffolding proteins important for synaptic and cellular junctions belong to the large family of membrane-associated guanylate kinases (MAGUK). In order to elucidate the origin and the evolutionary history of the MAGUKs we investigated full-length cDNA, EST and genomic sequences of species in major phyla. RESULTS: Our results indicate that at least four of the seven MAGUK subfamilies were present in early metazoan lineages, such as Porifera. We employed domain sequence and structure based methods to infer a model for the evolutionary history of the MAGUKs. Notably, the phylogenetic trees for the guanylate kinase (GK)-, the PDZ- and the SH3-domains all suggested a matching evolutionary model which was further supported by molecular modeling of the 3D structures of different GK domains. We found no MAGUK in plants, fungi or other unicellular organisms, which suggests that the MAGUK core structure originated early in metazoan history. CONCLUSION: In summary, we have characterized here the molecular and structural evolution of the large MAGUK family. Using the MAGUKs as an example, our results show that it is possible to derive a highly supported evolutionary model for important multidomain families by analyzing encoded protein domains. It further suggests that larger superfamilies encoded in the different genomes can be analyzed in a similar manner.